The financial crisis as a tsunami Discourse profiles of economists in the financial crisis - Stephan Pühringer; Katrin Hirte (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2013)
The article analyses the role of economists in public discourse with regard to the financial crisis. Specifically, it focuses on the prevailing rhetorical strategies and the economic convictions of leading German - speaking economists as they appear in seven leading newspapers and magazines in the German - peaking area. Special attention is given to the prevailing rationales and explanations for the financial crisis as well as on the metaphors used for describing specific economic events in particular and the market economy in general. The results of this article show that while the financial crisis could have offered a possibility for a paradigm shift in economic thinking, there is not much evidence for such a shift among German - speaking economists. The observed stability of the dominant paradigm is attributed primarily to the very stable role of certain basic economic convictions, which are exposed through the use of specific metaphors as well as a characterization of the financial crisis as a (series of) extraordinary and exogenously given event(s). (e.g. "a tsunami")
Keywords: A11; A14; G01; Z13; 330; Financial Crisis; Failure of Economics; Economic Mainstream; Metaphor Analysis; Discourse Analysis